Pelatihan Membatik Aksara Incung Membagun Jiwa Kewirausahaan Bagi Generasi Muda Kota Sungai Penuh dan Kabupaten Kerinci - Ravico; DS, Muhammad Ridha; Siregar, Anggi Desviana (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2023)
There is data indicating a continuous increase in the workforce, especially with the rising number of high school graduates each year, both at the provincial level in Jambi and in the city of Sungai Penuh. Faced with this situation, one proposed solution is through entrepreneurship empowerment. It is hoped that the Community Service Program can generate new entrepreneurs by involving a series of activities, ranging from planning, production processes, to the marketing of Aksara Incung batik. This is considered a contribution to addressing workforce growth issues and enhancing the skills of the younger generation. The Community Service Program is expected to be able to give birth to new entrepreneurs through a series of planning activities and processes leading to the implementation of the production and marketing process of incung batik. The community service method used is the Asset-Based Community Development (ABCD) method. The ABCD approach aims to develop an Asset-Based Community (potential), such as developing an educational community, an economy, and so on. The result of the service is the Incung script, which is typical of the cities of Sungai Penuh and Kerinci. Another angle is incung batik, which is a typical souvenir of Sungai Penuh. Until now, there has still been a shortage of incung batik craftsmen. The aspect of batik incung, as a distinctive souvenir of Sungai Penuh, still faces a shortage of craftsmen up to the present time. Particularly, the practice of batik incung craftsmen is mainly bound by traditional inheritance, and the product lacks innovation. With the presence of training, it is hoped to create improvement in the management of Human Resources, where Human Resources are considered as the main source or asset.Keywords: Include a maximum of three keywords or phrases